Identification of Candidate epitopes from nation-enriched sequences in the African swine fever virus genomes - Sieun Kim; Eun Bae Kim (PLoS ONE, 2026)
African swine fever virus (ASFV) is a highly lethal pathogen that causes African swine fever (ASF) and is found in Africa, Europe, and Asia. In addition, extensive regional genetic variation poses significant challenges for vaccine development. In this study, we aimed to identify amino acid sequence fragments that are commonly enriched within ASFV strains from each country and evaluate their potential as epitopes. Amino acid sequences of genomes were segmented into overlapping 9-, 12-, 15-, and 20-mer peptides; selected fragments enriched in countries with at least ten available genomes; and cytotoxic T lymphocyte (CTL), helper T lymphocyte (HTL), and linear B lymphocyte (LBL) epitope predictions, followed by antigenicity assessment. Genomes from Italy yielded the highest number of fragments across all peptide lengths, whereas those from Russia showed a unique pattern in which fragment counts decreased as peptide length increased. From the five countries analyzed, 136 CTL, 95 HTL, and 97 LBL candidate epitopes were identified, of which 39 CTL, 18 HTL, and 75 LBL epitopes were predicted to be antigenic. The identified epitopes originated from structural ( n = 24), replication/transcription ( n = 11), and multigene family ( n = 38) proteins. The resulting epitope library provides a comprehensive resource for the selection of multi target vaccines and diagnostic candidates. These findings provide a foundation for the design of region-specific vaccines and can be broadly applied for the future development of ASFV vaccines and diagnostic tools.